Internet connectivity disruption in France (France) - Voidly (2026)
CRITICAL severity disruption detected in France. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: FR-2026-0038
Keywords: internet disruption; FR; disruption; critical